Pengaruh Hukum terhadap Lima Kekuatan Persaingan Terkait dengan Perumusan Strategi Bersaing Menurut Michael E. Porter - Nugraha Pranadita; Ratih Hurriyati; Puspo Dewi Dirgantari (IPB University, 2021)
There are five competitive forces that influence the Industry. Industry competition affects business performance, so companies must adapt to changing environments to maintain a competitive position. One of the ways to win the competition is to use a strategy. Strategy allows organizations to gain a competitive advantage from three different foundations namely: cost leadership, differentiation and focus. Strategic planning can help to develop an early warning system to avoid threats or develop strategies that can turn threats into profits for the company. Thus the strategy can maximize competitive advantage on the one hand, and can minimize the limitations of competing. The question is; How do laws and regulations affect Porter's five competitive forces and the three generic strategies? This research is a qualitative analytical descriptive study using secondary data, and the unit of analysis is the prevailing laws and regulations in Indonesia. The results of this study; consistently statutory regulations (laws) influence the five competitive forces and three generic strategies put forward by Porter.